HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL TRIMESTER III - Riska Winarni; Gumiarti; Eni Subiastutik (Akademi Kebidanan Aifa Husada Madura, 2023)
Antenatal Care is a program carried out by health workers to provide health services for pregnant women with the aim of monitoring and detecting early health problems for the mother and fetus. Some third trimester pregnant women have a low level of knowledge so that the achievement of K4 coverage of third trimester pregnant women with at least 3 visits for antenatal care examinations in the Jenggawah health center area still reaches the target of 74.7% of the target of 100%. The research design uses cross sectional. The population was 41 third trimester pregnant women with 37 samples. Cluster random sampling was taken. Measuring tool is questionnaire and test analysis Chi Square. The results showed that 6 (16.2%) had good knowledge, 11 (29.7%) sufficient knowledge, 20 (54.1%) insufficient knowledge. Compliance with antenatal care visits 24 (64.9%) adherents and 13 (35.1%) non-compliant. The results of the analysis test showed that the p-value was 0.006 <α 0.05, which means that there is a relationship between the level of knowledge and adherence to antenatal care visits, namely good knowledge and being able to increase adherence to antenatal care visits. The role of health workers, especially midwives, is more active and communicative in encouraging pregnant women to take antenatal care so that they can increase compliance with antenatal care visits.